Analisis Kegiatan Pengelolaan Kurikulum di UPT SDN 31 Koto Pulai (Indo-MathEdu Intellectuals Journal, 2025)
The curriculum plays a crucial role in the education system, serving as a tool to achieve the educational goals that have been set. The Independent Curriculum, which was introduced in 2020 and began to be implemented in 2022, however, its implementation in the field is still uneven. This study aims to find out the curriculum management activities at UPT SDN 31 Koto Pulai. This research is a type of descriptive qualitative research with observation and interview techniques as the main data collection techniques. The data was analyzed qualitatively with the stages of data reduction, data presentation, and conclusion drawing and verification. The results of the analysis show that good Curriculum management is very important to ensure the effectiveness of learning, which includes planning, development, implementation, and assessment. The planning process at UPT SDN 31 Koto Pulai involves a meeting between the principal and educators to discuss the needs and combination of the curriculum. Curriculum development is carried out by formulating the vision, mission, and program structure, as well as organizing learning activities. The implementation of the curriculum in this school focuses on the application of learning tools that are in accordance with the applicable curriculum, with an interactive and collaborative approach. Through the Teacher Working Group (KKG) training, the school strives to improve the quality of teaching